Age assessment for unaccompanied asylum-seeking children in Egypt - Zavala Folache, C; Ritchie, B (Refugee Studies Centre, University of Oxford, 2020)
Incorrectly processing a child’s asylum claim as an adult’s as a result of an age assessment fails to give due weight to child-specific vulnerabilities and may affect the integrity and outcome of the RSD process.